Appropriate Simulation Technique for Complete Single-Bolt Shear Connection Shear-Out Tensile Properties and Fracture Behavior Predictions (2 (2019)
This paper presents the finite element (FE) predictions of the complete S235, S690, Q550D, Q690D and Q890D steel grades steel sheet single-bolt shear connections shear-out (SBSCSO) behavior (tensile properties and fracture behavior). This work reveals that the FE elastic–plastic simulations without the damage and fracture model generally employed in the literature for SBSCSO failure predictions cannot predict the post-ultimate-load damage behavior, fracture initiation by elements removal and sudden drops in load required for determining the SBSCSO displacement at fracture. Consequently, the FE simulation without the damage and fracture model cannot accurately predict the complete SBSCSO tensile properties and fracture behavior. In particular, the FE simulation without the damage and fracture model cannot predict the SBSCSO displacement at fracture required for the seismic and fracture-resistant designs needed for the prevention of the failure of single-bolt shear connections that exhibit the shear-out fracture under extreme loading. FE simulation with the elastic, plastic damage and fracture models represents the appropriate simulation technique for the complete SBSCSO tensile properties and fracture behavior predictions.